Measurement of Some non-routine Markers in Patients with Chronic Kidney Disease - Haider Ali Laibi; Abdulkareem M. Jawad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Chronic kidney disease has an indirect effect on global disorder and death by raising the risks of morbidityand mortality . This study included (60) patient diagnosed chronic renal failure; it also included (25)healthy subjects as control . In study population age ranged from (14-65 years) old who visited Al-BasrahTeaching Hospital in Basrah throughout the period from October 2020 to February 2021. Enzyme-LinkedImmunosorbent Assay (ELISA) was used to measure human serum soluble alpha klotho proteins , irisin andcystatin C . The results showed that there is a high significant difference (P value < 0.01) in the levels betweenCKD patients and control for the following : Soluble-a-klotho protein; Irisin (ng/ml) ; Cystatin-C (ng/ml).There was also a high significant decrease in the levels of irisin (ng/ml)among different stages of chronickidney . The same table revealed a high significant increase (P value <0.01) in the levels of Cystatin-C (ng/ml) and Soluble-a-klotho protein (ng/ml) among different stages of chronic kidney and respectively) . Thestudy concluded that there is a remarkable decrease in the level of serum soluble alpha klotho proteins andirisin and increase in serum cystatin C in patients with chronic kidney disease ; and these differences arepositively correlated with the glomerular filtration rate .